Emotions related to physical education lessons in students with intellectual disabilities - Wieczorek, Marta; Sadziak, Aleksandra; Karásková, Vlasta (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical education is an area that is essential for the comprehensive development of individuals with intellectual disabilities. Physical exercises through the diversity of their forms impact motor fitness improvement, develop and enhance natural motor function, and have a positive effect on the development of personality traits, all of which can increase the number of opportunities for good social function. This process is more effective if accompanied by positive emotions, reactions. Aim of Study. The study had two aims; first, to determine the emotional responses to physical education lessons experienced by students with intellectual disabilities; and second, to compare the performance of students with intellectual disabilities to those of their intellectually non-disabled peers. Material and Methods. The study was conducted on two cohorts of students born between 2001 and 2003: the first were individuals with light and moderate intellectual disabilities from special schools; the second group were intellectually non-disabled students from mainstream schools. A diagnostic survey was applied as a research method, whereas an interview was the technique used. The DEMOR Survey on Emotional Response to Physical Education at School by Svoboda was a research tool used for the purpose of this investigation. Results. Among positive emotional responses common to students of both special schools and mainstream schools, relaxation, self-confidence as well as a sense of successful task completion predominate. The examined intellectually non-disabled students are more likely to note positive emotional responses experienced during physical education lessons than students with intellectual disabilities. Conclusions. Physical education lessons are accompanied by substantial emotional involvement. More frequently, it is a source of positive emotional responses, which makes the process of physical education more effective and increases the results of psychophysical development in students.
Keywords: intellectual disability; physical education; emotions